Abrogation and appropriation in selected pre-war Philippine short stories in English - Quinto, Edward Jay Mansarate; Santos, Juan Carlos (Penerbit Universiti Kebangsaan Malaysia, 2016)
Postcolonial literature is characterized by abrogation and appropriation, in which writers take the language of the former imperial power and re-place it in a discourse fully adapted to the colonized place. Studies on literary traditions of former colonies have shown how native writers advance local collective sentiments. In this paper, the short stories of Manuel Arguilla, a literary icon of Philippine short stories in English, were analyzed using Ashcroft et al.’s (1989) textual strategies in postcolonial writing to unearth the strategies used by the writer in valorizing the use of an abrogated and appropriated “english” in expressing native sentiments. Qualitative content analysis of Arguilla’s four short stories suggests that the use of untranslated words and glossing were the most abundant strategies used to abrogate and appropriate the colonizer’s language. Further, thematic analysis of the stories point to four themes relating to how the author valorized the use of an english in expressing native sentiments: expression of an authentic self, expression of an authentic place, subtle form of subversion and advancement of Filipino identities and ideologies. These findings suggest that, like in other postcolonial literary traditions, postcolonial Philippine short stories, as seen from the writing of Manuel Arguilla, are typical of what Ashcroft et al. (1989) advance as a paradigmatic tension between the colonizer and the colonized, but are unique in that they serve as medium through which to voice out local Filipino sentiments and aspirations. Some implications for postcolonial literature are discussed.